Matching The Competencies Of Hospitality Graduates With The Expectations From The Hospitality Industry In Ghana: A Case Study - Commey, Vida (Central University of Technology, 2021)
Employers in the hospitality industry worldwide are expecting graduates to be work-ready, possessing competencies that will assist them to achieve their ultimate goal of profit maximization. Universities therefore must assess the competency needs of specialized areas within the industry and incorporate them into their curriculum. The purpose of this study was to match the competencies of hospitality graduates with the expectations from industry in the Ghanaian context. The main aim of the study was to contribute both theoretically and empirically by addressing the challenges of training and developing suitably qualified hospitality graduates. The data for this study were collected in two phases, incorporating both quantitative and qualitative methods. In the quantitative phase, a structured questionnaire was administered to collect data from both university graduates and hospitality employers. In the qualitative phase, focus group interviews were conducted to collect data from stakeholders, including heads of hospitality departments and hospitality management lecturers of five selected technical universities in Ghana. In the quantitative phase, data were analyzed using descriptive and inferential statistics with the help of the Statistical Package for Social Sciences (IBM SPSS) version 23. In the qualitative phase, thematic content analysis was used to analyze the data. The empirical results revealed that the key competencies expected of hospitality graduates were leadership skills, teamwork, communication skills, human relations/ interpersonal skills, operational skills, problem-solving skills, innovative abilities, right attitude towards work, and the ability to adapt to challenging circumstances. However, with regard to the extent to which hospitality graduates exhibit the required competencies, a Mann-Whitney U test indicated that, according to hospitality employers, none of the required competencies were exhibited by hospitality graduates. The findings thus revealed gaps between the competencies expected by the industry and the perceived competencies of hospitality graduate. These gaps can, in part, be attributed to current hospitality curricula being offered by Ghanaian universities. Based on these gaps, the study proposed a framework for hospitality management programmes to address the shortcomings. The study further emphasized the need for universities that offer hospitality management programmes to assess the competencies desired by the tourism and hospitality industry to produce graduates who are able to meet the needs of the job market.
Thesis
Keywords: Tourism and Hospitality Industry; Hospitality Graduates; Hospitality Industry Employers; Competencies; Hospitality Industry Expectations; Case Study Research; Competency Framework; Ghana; Technical Universities; Industry Expectation